2018
DOI: 10.1093/mnras/sty365
|View full text |Cite
|
Sign up to set email alerts
|

A D’-type symbiotic binary in the planetary nebula SMP LMC 88

Abstract: SMP LMC 88 is one of the planetary nebulae (PN) in the Large Magellanic Cloud. We identify in its spectrum Raman scattered O vi lines at 6825 and 7083Å. This unambiguously classifies the central object of the nebula as a symbiotic star (SySt). We identified the cold component to be a K-type giant, making this the first D'-type (yellow) SySt discovered outside the Galaxy. The photometric variability in SMP LMC 88 resembles the the orbital variability of Galactic D'-type SySt with its low amplitude and sinusoida… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…Symbiotic classification of Gaia18aen is also supported by its position in diagnostic diagram using [O iii] and Balmer lines fluxes and in the He i diagram (for more details see e.g. Iłkiewicz et al 2018a). In both diagrams (see Fig.…”
Section: Spectral Features and Symbiotic Classificationmentioning
confidence: 82%
“…Symbiotic classification of Gaia18aen is also supported by its position in diagnostic diagram using [O iii] and Balmer lines fluxes and in the He i diagram (for more details see e.g. Iłkiewicz et al 2018a). In both diagrams (see Fig.…”
Section: Spectral Features and Symbiotic Classificationmentioning
confidence: 82%
“…Moreover, the object is classified as a symbiotic binary in all seven classification trees suggested by Akras et al (2019b) to distinguish between symbiotic stars and common mimics. The lack of [O III] lines in the spectra of DeGaPe 35 precludes the use of diagnostic diagrams based on the [O III] and Balmer lines fluxes (e.g., Iłkiewicz Mikołajewska, 2017;Iłkiewicz et al, 2018). We have employed the He I diagram (Fig.…”
Section: Symbiotic Naturementioning
confidence: 99%
“…This question is not rhetorical, as several direct and indirect observational evidence indicate that mass accretion takes place in several binary central stars of PNe. For instance, binary systems related to accreting WDs such as classical novae (Bode et al 1987;Wesson et al 2008), symbiotic stars (Guerrero et al 2004;Santander-García et al 2004;Corradi et al 2011;Munari et al 2013;Iłkiewicz et al 2018;Akras et al 2019) and supersoft X-ray sources (Kahabka et al 2008;Hutchings et al 2001;Mereghetti et al 2010;Maitra & Haberl 2022) have been observed to be hosted in the centres of PNe. Mass accretion processes have also been suggested to take place at the central stars of the PNe N66 (Hamann et al 2003) and the Eskimo Nebula (Guerrero et al 2019) as a plausible explanation for the two optical outbursts and the variable X-ray emission observed at the centre of the two nebulae, respectively.…”
Section: Introductionmentioning
confidence: 99%